Manfaat Teknologi Di Bidang Pendidikan Dan Ekonomi - M.Fazli Harsya; Muhammad Aditya Setiawan; Raja Ferdiansyah Siregar; Muhammad Faiz Ridho; Muhammad ferdy zega; Said Hambali Takhir (Journal Of Informatics And Busisnes, 2026)
Information systems have become an essential component in organizational activities, particularly in managing data and supporting decision-making processes. Along with the rapid advancement of information technology, a clear understanding of the role of information systems and the technologies that support them is increasingly important. This study aims to examine the role of information systems and to identify supporting technologies that contribute to organizational effectiveness and efficiency. The research adopts a descriptive qualitative approach through a literature review by analyzing relevant scientific publications. The findings indicate that information systems play a role in data processing, information delivery, and decision support. Technologies such as database systems, web-based applications, and decision support systems are widely used to enhance operational performance. This study provides a conceptual overview that may serve as a reference for future studies and for organizations seeking to better utilize information systems.